2016
DOI: 10.3389/fmicb.2016.01472
|View full text |Cite
|
Sign up to set email alerts
|

The Terrestrial Isopod Microbiome: An All-in-One Toolbox for Animal–Microbe Interactions of Ecological Relevance

Abstract: Bacterial symbionts represent essential drivers of arthropod ecology and evolution, influencing host traits such as nutrition, reproduction, immunity, and speciation. However, the majority of work on arthropod microbiota has been conducted in insects and more studies in non-model species across different ecological niches will be needed to complete our understanding of host–microbiota interactions. In this review, we present terrestrial isopod crustaceans as an emerging model organism to investigate symbiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 167 publications
5
97
0
1
Order By: Relevance
“…In particular, the functional groups of beta proteobacteria are not only similar to each other, but also statistically not dissimilar to group a of alpha and group b of alpha and gamma proteobacteria (Fig 4C), even if their visual comparison does shows some distinctive features (Fig 5B). Statistically significant levels of similarity between functional groups from different proteobacterial classes can be interpreted in terms of functional redundancy, a pattern previously found in diverse microbiomes [3,5,30,42,45]. Functional redundancy, together with the correspondence between functional groups and taxonomic clusters (for groups a, b and c in Fig 1, groups a and c in Fig 2 and group c in Fig 3), are consistent with the concept that environmental filtering could be the major driving force for structuring microbiomes [3,5,18,30].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, the functional groups of beta proteobacteria are not only similar to each other, but also statistically not dissimilar to group a of alpha and group b of alpha and gamma proteobacteria (Fig 4C), even if their visual comparison does shows some distinctive features (Fig 5B). Statistically significant levels of similarity between functional groups from different proteobacterial classes can be interpreted in terms of functional redundancy, a pattern previously found in diverse microbiomes [3,5,30,42,45]. Functional redundancy, together with the correspondence between functional groups and taxonomic clusters (for groups a, b and c in Fig 1, groups a and c in Fig 2 and group c in Fig 3), are consistent with the concept that environmental filtering could be the major driving force for structuring microbiomes [3,5,18,30].…”
Section: Resultsmentioning
confidence: 92%
“…Statistically significant levels of similarity between functional groups from different proteobacterial classes can be interpreted in terms of functional redundancy, a pattern previously found in diverse microbiomes [3,5,30,42,45]. Functional redundancy, together with the correspondence between functional groups and taxonomic clusters (for groups a, b and c in Fig 1, groups a and c in Fig 2 and group c in Fig 3), are consistent with the concept that environmental filtering could be the major driving force for structuring microbiomes [3,5,18,30]. To illustrate the functional redundancy across the taxonomic spectrum of bacterial microbiomes [3], the functional groups of all proteobacterial classes have been graphically compared from deep to late branching taxa along both orthogonal axes (Fig 5B).…”
Section: Resultsmentioning
confidence: 92%
“…We propose that food resource abundance and diversity in the local habitat could be one of the main drivers for both gut bacterial richness and host fat content. Further, diet‐related bacteria can potentially affect host fitness directly when they serve as a supplemental food source, temporarily contribute to digestion processes (Bouchon et al., ) or facilitate adaption to novel food sources (Chu, Spencer, Curzi, Zavala, & Seufferheld, ). However, if and to what extend a predator benefits from a mixed diet (Evans, Stevenson, & Richards, ; Harwood et al., ; Lefcheck, Whalen, Davenport, Stone, & Duffy, ; Lundgren, ) and diverse gut bacteria depends on host species: In our study, the two native beetles H. convergens and H. parenthesis had more body fat when their guts harbored many different bacterial.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes can be vertically transmitted or acquired from the environment (horizontal transmission; Gibson & Hunter, ; Mason & Raffa, ). In addition, the total gut community also includes transient species that cannot permanently colonize the gut (Dillon, Vennard, Buckling, & Charnley, ; Erkosar & Leulier, ) but may represent a supplementary food source, or contribute to digestion (Bouchon, Zimmer, & Dittmer, ). Understanding factors influencing animal gut microbiome composition can thus yield important insights into ecological interactions.…”
Section: Introductionmentioning
confidence: 99%
“…7 The insect gut, in particular, harbors a vast array of symbiotic microbial diversity and many studies have demonstrated the profound importance of these associations on insect digestive and immune systems. 812 Studies of these systems have been remarkably productive. Importantly, such studies with insects have curiously, served as a prelude to more recent efforts focused on human-microbe symbioses in which in vivo generated natural products play a clear role in human health.…”
Section: Animal-microbe Symbiosesmentioning
confidence: 99%